2012
DOI: 10.1186/1471-244x-12-79
|View full text |Cite
|
Sign up to set email alerts
|

Perceived causes of severe mental disturbance and preferred interventions by the Borana semi-nomadic population in southern Ethiopia: a qualitative study

Abstract: BackgroundCulture affects the way people conceptualize causes of severe mental disturbance which may lead to a variation in the preferred intervention methods. There is a seemingly dichotomous belief regarding what causes severe mental disturbance: people living in western countries tend to focus mainly on biological and psychosocial risk factors; whereas, in non-western countries the focus is mainly on supernatural and religious factors. These belief systems about causation potentially dictate the type of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 33 publications
11
69
0
Order By: Relevance
“…This justification for this might be that participants who think of mental illness as a severe form might take seek help from modern treatment than the traditional one. Besides, in our community, people think that the modern form of treatment for mental illness is the last preserved option for severe mental illness [11]. Besides, participants whose age group was from 25-34 years were 1.46 times at higher odds of having an intention to seek help from traditional forms of help than participants whose ages ranged from 18-24 years.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This justification for this might be that participants who think of mental illness as a severe form might take seek help from modern treatment than the traditional one. Besides, in our community, people think that the modern form of treatment for mental illness is the last preserved option for severe mental illness [11]. Besides, participants whose age group was from 25-34 years were 1.46 times at higher odds of having an intention to seek help from traditional forms of help than participants whose ages ranged from 18-24 years.…”
Section: Discussionmentioning
confidence: 94%
“…Also, in some areas, people left clients who have mental illness alone if he/she did not respond to informal help source and modern treatments. Based on the patient's condition, he/she chose to live with the family getting his/her basic needs or wander around the street naked [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conceptualization and perceived cause of mental illness vary from community to community. Accordingly, people with mental health problem get different names in different societies [46]. …”
Section: Introductionmentioning
confidence: 99%
“…Community based studies conducted in Ethiopia revealed that common mental disorders are highly prevalent in the society ranging from 11.7-22.7% [15][16][17]. And traditional measures have been the most preferred treatment option [18,19]; because of the belief that mental illness is a related to a consequence of a sinful act [20][21][22].…”
Section: Introductionmentioning
confidence: 99%